Hubungan Pola Makan Dengan Status Gizi Balita Usia 1-3 Tahun di Kelurahan Tanjung Mulia Kota Medan Tahun 2025 - Mestika Rija Helti; Nila Hayati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The nutritional status of toddlers reflects a child's health and nutritional adequacy based on nutrient intake and their body's needs. In infants aged 1-3 years, nutritional status reflects the balance between nutritional intake and nutritional needs to support physical growth, brain development, and other bodily functions. This study aims to determine the relationship between dietary patterns and the nutritional status of toddlers aged 1-3 years at the subdistrict, 2025. The research method used was quantitative research with a non-experimental cross-sectional design. The population consisted of 80 respondents, with a sample of 33 mothers with toddlers aged 1-3 years old selected using purposive sampling. Data collection was conducted using questionnaires and anthropometric data. Data were analyzed univariately and bivariately using the Spearman rank test. The results showed that the majority of mothers had an adequate diet (48.5%), and the majority were in the normal weight category (51.5%). The Spearman rank test statistically showed a correlation between diet and nutritional status. The p-value was 0.004 (p<0.05) and r=0.489. Therefore, H0 was rejected and Ha was accepted. The conclusion of this study is that there is a significant relationship between diet and nutritional status of toddlers aged 1-3 years old. Therefore, it is recommended to improve nutritional education for toddlers to ensure they are able to provide appropriate dietary patterns to support optimal growth and development.